2011
DOI: 10.1097/aco.0b013e32834a12a1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anesthesia on cerebral blood flow, cerebral metabolic rate, and brain functional connectivity

Abstract: Accumulating evidence suggests that hypnotic anesthetic agents disrupt large-scale cerebral connectivity. This would result in an inability of the brain to generate and integrate information, while external sensory information is still processed at a lower order of complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Previous studies demonstrated diverse effects of anesthesia on resting-state brain connectivity Bonhomme et al, 2011Bonhomme et al, , 2012Hudetz, 2012;Nallasamy and Tsao, 2011). The early work of Kiviniemi and associates (2005) indicated that sedative levels of the intravenous anesthetic, midazolam enhanced the amplitude and synchrony of spontaneous BOLD signal fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated diverse effects of anesthesia on resting-state brain connectivity Bonhomme et al, 2011Bonhomme et al, , 2012Hudetz, 2012;Nallasamy and Tsao, 2011). The early work of Kiviniemi and associates (2005) indicated that sedative levels of the intravenous anesthetic, midazolam enhanced the amplitude and synchrony of spontaneous BOLD signal fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a rapidly expanding group of investigators began to approach the problem by applying anesthetic agents to reversibly modulate the state of consciousness in search of unique neuronal correlates of state transitions in the brain in both humans and animals Boly et al, 2013;Bonhomme et al, 2012;Brown et al, 2010;Hudetz, 2012;Mashour and Alkire, 2013). Tentative findings have suggested a role for large-scale thalamocortical and corticocortical networks, subcortical modulatory and higher cortical integration centers in the orchestration of the reversible transitions between conscious and unconscious states (Alkire, 2008;Bonhomme et al, 2011;Boveroux et al, 2010;Ferrarelli et al, 2010;Guldenmund et al, 2013;Hudetz, 2012;Langsjo et al, 2012;Lee et al, 2009aLee et al, , 2009bLee et al, , 2013Mhuircheartaigh et al, 2010;Nallasamy and Tsao, 2011;Peltier et al, 2005;Schrouff et al, 2011;White and Alkire, 2003). However, a final common pathway or unitary theory for losing and regaining consciousness has not emerged.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that anesthesia has a significantly weaker influence in early sensory cortical areas and very likely in the downstream spinal cord than higher order cognitive brain regions (for a review, see ref. 34). We believe that anesthesia is unlikely a major influence on the horn-to-horn connectivity differences between anesthetized monkeys and awake humans (4,5) or before and after injury.…”
Section: Discussion Widespread Fmri Responses To Noxious Stimuli Withmentioning
confidence: 99%
“…15 Among companion dogs, most Chihuahuas have a molera of the head, and the lacuna may remain open throughout life. Therefore, we realized that a Chihuahua molera is a boneless locus and, consequently, NIRS beams easily reach the cerebral cortex by passing through the molera in the scalp, and is, therefore, ideal for a pilot study of canine brain NIRS in conscious state.…”
Section: Introductionmentioning
confidence: 99%